First principle investigation on the thermal stability of a golden fullerene: a case study of Au-32 - De, Himadri Sekhar; Krishnamurty, Sailaja; Pal, Sourav (Catalysis Today, 2012)
Structural and electronic properties of Au-32 cluster are analyzed using relativistic density functional theory (DFT) based methods. Further, DFT based molecular dynamical (MD) simulations are performed on Au-32 golden fullerene with an aim of understanding its thermal stability at various working temperatures. Various conformations being populated at different temperatures of a cluster are analyzed. The study shows that the ground state icosahedral conformation is stable only up to 300 K and structure remains in a hollow conformation only up to 400 K. This clearly explains the reasons for failure by experimentalists in trapping the unique fullerene conformation in spite of the theoretical predictions of it being a very stable one. The above MD study also indicates that the bare fullerene Au-32 cluster (without any stabilizing ligands) can be used for potential catalytic applications only around room temperatures. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Au-32 cluster; Born-Oppenheimer molecular dynamics; Density functional theory; Golden fullerenes; Relativistic effects